Validação do diagnóstico de enfermagem estilo de vida sedentário em universitários - Fernandes, Renata Marinho (2024)
Lifestyle is a modifiable and determining factor in preventing illness. However, university students are mentioned as a vulnerable group for sedentary behavior. Therefore, the present study aims to analyze evidence of the validity of the nursing diagnosis Sedentary lifestyle in university students.This is a methodological research, developed in two stages: content analysis of the aforementioned diagnosis, proposed from a middle-range theory developed in a previous study; and clinical validation. The first stage was carried out during the first semester of 2023, with 48 judges. The judges were categorized into levels of expertise. For statistical analysis, the content validity index was calculated using the Wilcoxon test. In the second stage, a crosssectional diagnostic accuracy study was carried out in the second semester of 2023. The study included 108 undergraduate students in Nursing at the Federal University of Rio Grande do Norte. The sociodemographic and clinical numerical data were listed by mean, standard deviation, median, minimum and maximum. For the categorical variables, the relative and absolute frequencies were recorded. To establish the sensitivity and specificity measures, the latent class model with random effects was applied. The study was approved by the Research Ethics Committee. The results of the content analysis identified four defining characteristics, eight related factors, four populations at risk and one associated condition. They were further improved in terms of robustness, clarity and operability. Regarding clinical validation, the prevalence of the nursing diagnosis Sedentary lifestyle in young adult university students was 16.3%. Thus, “inadequate sleep quality” was identified as a sensitive characteristic and “lack of physical fitness” and “cardiovascular alterations” as specific characteristics. Furthermore, seven related factors were prevalent, namely: “socially imposed behaviors on the female gender”, “unfavorable environmental conditions for physical activity”, “unfavorable climatic conditions for physical activity”, “deficient knowledge about sedentary lifestyle”, “family history of sedentary lifestyle”, “prolonged sitting time ≥8h” and “excessive screen time ≥3h”. And three populations at risk: “university students”, “young adults” and “individuals living in urban areas” in the sample analyzed. It is concluded that the nursing diagnosis Sedentary lifestyle is valid for university students and presents three defining characteristics with good accuracy. Thus, based on a greater theoretical basis, it is expected to contribute to the development of health actions in the university environment and, thus, promote the adoption of healthier lifestyles, as well as contribute to increasing the level of evidence of this diagnosis in the NANDA-I taxonomy.